Pengaruh Akuntabilitas Dan Profesionalisme Terhadap Kualitas Audit Dengan Due Professional Care Sebagai Variabel Moderasi - Bisma Ainun Pradana; Sri Trisnaningsih (Journal of Economic, Bussines and Accounting (COSTING), 2022)
The auditor profession is a profession that is trusted by the public so that it requires an attitude of accountability, professionalism, and due professional care in ensuring the quality of the resulting audit. This study aims to measure the relationship provided by accountability and professionalism to audit quality with due professional care as a moderating variable. This study uses a quantitative approach. The sample in this study is auditors who work at Public Accounting Firms in the East Surabaya area. The type of data used in this study is primary data in the form of questionnaires filled out by respondents. The analysis technique used is Partial Least Square (PLS). The results of this study indicate that accountability and professionalism are proven to affect audit quality. Due professional care can moderate the relationship between accountability and audit quality, but cannot moderate the relationship between professionalism and audit quality. Keywords: accountability, professionalism, quality of audit, due profesiional care